Why not nursing? Factors influencing healthcare career choice among Singaporean students. (19th September 2016) - Liaw, S.Y.; Wu, L.T.; Holroyd, E.; Wang, W.; Lopez, V.; Lim, S.; Chow, Y.L.
Abstract : Background: Internationally, and particularly in Singapore, health education institutions are facing challenges in attracting school leavers to enter nursing courses. Objectives: To identify the factors influencing the career choice of Singaporean healthcare students and determine the deterrents in choosing nursing as a career choice. Design: An exploratory descriptive qualitative study design was used. Participants: Fifty‐nine healthcare students from three higher education institutions were recruited. Method: Four nursing and four non‐nursing focus groups discussion were held. Interview transcripts were analysed using thematic analysis. Results: Six themes emerged as follows: 'personal interest'; 'prior healthcare exposure'; 'job prospects'; 'academic performance'; 'perceived nature of work'; and 'social influences'. Discussion: The personal interests to help and care along with prior healthcare exposures were found to influence the students' choice. Job prospects such as the ease of getting a job, job stability, and job salary were considered. Nursing was perceived as a course for students with poor academic ability. Misconceptions about the nature of work and a lack of social recognition were identified as deterring factors in students' choice of nursing as a career. Conclusions: An understanding of the career decision process among healthcare students enables educational leaders and policy‐makers to enhance the focus of nursing recruitment strategies. Implications for nursing and/or health policy: Strategies for nursing recruitment in Singapore must include creating more opportunities for exposure to nursing in early school years, reviewing the admission policies for nursing programmes to attract academically abled students, ensuring that nursing graduates' salaries are comparable with other healthcare graduates, promoting a better understanding on the role of a registered nurse and its career developments, and providing support for those who are interested in nursing but are faced with career decision‐making difficulties due to their families.